Near infrared fluorescence-guided real-time endoscopic detection of peritoneal ovarian cancer nodules using intravenously injected indocyanine green - Kosaka, Nobuyuki (2011)
Near infrared fluoresce-guidance can be used for the detection of small cancer metastases and can aid in the endoscopic management of cancer. Indocyanine green (ICG) is an FDA-approved fluorescence agent. Through non-specific interactions with serum proteins, ICG achieves enhanced permeability and retention (EPR) effects. Yet, ICG demonstrates rapid clearance from the circulation. Therefore, ICG may be an ideal contrast agent for real-time fluorescence imaging of tumors. To evaluate the usefulness of real-time dual fluorescence and white light endoscopic optical imaging to detect tumor implants using the contrast agent ICG, fluorescence-guided laparoscopic procedures were performed in mouse models of peritoneally disseminated ovarian cancers. Animals were administered intravenous ICG or a control contrast agent, IR800-conjugated to albumin. The ability to detect small ovarian cancer implants was then compared. Using the dual view microendoscope, ICG clearly enabled visualization of peritoneal ovarian cancer metastatic nodules derived from SHIN3 and OVCAR5 cells at 6 and 24 h after injection with significantly higher tumor-to-background ratio than the control agent, (IR800-albumin p<0.001). In conclusion, ICG has the desirable properties of having both EPR effects and rapid clearance for the real-time endoscopic detection of tiny ovarian cancer peritoneal implants compared to a control macromolecular agent with theoretically better EPR effects but longer circulatory retention. Given that ICG is already FDA-approved and has a long track record of human use, this method could be easily translated to the clinic as a robust tool for fluorescence-guided endoscopic procedures for the management and treatment of cancer.